Environment, labour and capitalism at sea : 'Working the ground' in Scotland - Howard, Penny McCall (Book collections on Project MUSE., 2017)
This book explores how fishers make the sea productive through their labour, using technologies ranging from wooden boats to digital GPS plotters to create familiar places in a seemingly hostile environment. It shows how their lives are affected by capitalist forces in the markets they sell to, forces that shape even the relations between fishers on the same boat. Fishers frequently have to make impossible choices between safe seamanship and staying afloat economically, and the book describes the human impact of the high rate of deaths in the fishing industry. The book makes a unique contribution to understanding human-environment relations, examining the places fishers create and name at sea, as well as technologies and navigation practices. It combines phenomenology and political economy to offer new approaches for analyses of human-environment relations and technologies. --